Combination of adipose-derived mesenchymal stem cells (ADMSC) and ADMSC-derived exosomes for protecting kidney from acute ischemia–reperfusion injury. (1st August 2016) - Lin, Kun-Chen; Yip, Hon-Kan; Shao, Pei-Lin; Wu, Shun-Cheng; Chen, Kuan-Hung; Chen, Yen-Ta; Yang, Chih-Chao; Sun, Cheuk-Kwan; Kao, Gour-Shenq; Chen, Sheng-Yi; Chai, Han-Tan; Chang, Chia-Lo; et al.
Abstract: Background: In this study, we tested the hypothesis that a combined adipose-derived mesenchymal stem cell (ADMSC) and ADMSC-derived exosome therapy protected rat kidney from acute ischemia–reperfusion (IR) injury (i.e., ligation of both renal arteries for 1 h and reperfusion for 72 h prior to euthanization). Methods and results: Adult-male SD rats (n = 40) were equally categorized into group 1 (sham control), group 2 (IR), group 3 [IR + exosome (100 μg)], group 4 [IR + ADMSC (1.2 × 10 6 cells)], and group 5 (IR-exosome-ADMSC). All therapies were performed at 3 h after IR procedure from venous administration. By 72 h, the creatinine level and kidney injury score were the lowest in group 1 and the highest in group 2, significantly higher in group 3 than in groups 4 and 5, and significantly higher in group 4 than in group 5 (all P  < 0.0001). The protein expression of inflammatory (TNF-α/NF-κB/IL-1β/MIF/PAI-1/Cox-2), oxidative-stress (NOX-1/NOX-2/oxidized protein), apoptotic (Bax/caspase-3/PARP), and fibrotic (Smad3/TGF-β) biomarkers showed an identical pattern, whereas the anti-apoptotic (Smad1/5, BMP-2) and angiogenesis (CD31/vWF/angiopoietin) biomarkers and mitochondrial cytochrome-C showed an opposite pattern of creatinine level among the five groups (all P  < 0.001). The microscopic findings of glomerular-damage (WT-1), renal tubular-damage (KIM-1), DNA-damage (γ-H2AX), inflammation (MPO/MIF/CD68) exhibited an identical pattern, whereas the podocyte components (podocin/p-cadherin/synaptopodin) displayed a reversed pattern of creatinine level (all P  < 0.0001). Conclusion: Combined exosome–ADMSC therapy was superior to either one for protecting kidney from acute IR injury.